Pilot Investigation of Coal Chemical Wastewater Containing Phenol by Pervaporation Process - Jie, Yao; Yang, Shuren; Ziwei, Du; Biaoming, Li; Zhongwei, Wang; Agtmaal, Sjack van; Chunhui, Feng; Bangjun, Han (Journal of Membrane and Separation Technology, 2013)
Coal chemical wastewater contains a large number of industrial raw materials, such as phenol, resulting in difficulty as target to be treated and the resource waste as industrial raw materials. A pilot pervaporation process is investigated to separate and recycle phenols from coal chemical wastewater to reduce the follow-up biochemical processing load. Operation parameters which affect removing and recovering efficiency are studied, such as temperature, flow rate and downstream pressure. Phenol removal efficiency could reach 50% under the conditions of 70o C, 210 L/h and 3000 Pa. The system could continuously run for 20 cycles. Furthermore, the pervaporation procedure could be enhanced when pumped with gas which made the removal efficiency up to 66%.